1638: the Sovereign States - Flint, Eric; Huff, Gorg; Goodlett, Paula (Ring of fire (Riverdale, N.Y.), 2023)
"The United Sovereign States of Russia struggles to set in place the traditions and legal precedents that will let it turn into a constitutional monarchy with freedom and opportunity for all its citizens. At the same time, they're trying to balance the power of the states and the federal government. And the USSR is fighting a civil war with Muscovite Russia, defending the new state of Kazakh from invasion by the Zunghars, building a tech base and an economy that will allow its money to be accepted in western Europe, establishing a more solid claim to Siberia, and, in general, keeping the wheels of civilization from coming off and dumping Russia back into the Time of Troubles. Or, possibly even worse, reinstalling the sort of repressive oligarchy that they just got rid of"--